The Constitutional Court Judges' Legal Considerations on the Imposition of the Death Penalty - Gege, Sriwanto Arruan; Halwan, Muh.; Rusli, Muh. (Indonesian Journal Of Law Studies, 2025)
This study was conducted to analyze and determine the considerations of the Constitutional Court judges in the Constitutional Court's decision No. 2/PUU-V/2007 and how the rights of foreign citizens are protected in judicial review petitions against the 1945 Constitution of the Republic of Indonesia. The results of this study indicate that the Constitutional Court judges, in their considerations, stated that the death penalty under Law No. 10/2007 concerning the right to life is not absolute, and therefore, in certain cases, such as narcotics, the death penalty can still be imposed. Furthermore, for foreign citizens who file judicial review petitions against the 1945 Constitution, the provisions of Article 51 of Law No. 24 of 2003 concerning the Constitutional Court are based. Therefore, it is necessary to specifically regulate the protection of the rights of foreign citizens to file judicial review petitions against the 1945 Constitution.